2015
DOI: 10.1021/acs.langmuir.5b00177
|View full text |Cite
|
Sign up to set email alerts
|

New One-Step Thiol Functionalization Procedure for Ni by Self-Assembled Monolayers

Abstract: This article reports on a facile and fast strategy for the self-assembled monolayer (SAM) functionalization of nickel surfaces, employing cyclic voltammetry (CV) cycling of a suitable tailored solution containing the species to be adsorbed. Results are presented for ultrathin films formed on Ni by 1-hexadecanethiol (C16), L-cysteine (L-cys), and the poly{methyl (2R)-3-(2,2'-bithiophen-4-ylsulfanyl)-2-[(tert-butoxycarbonyl)amino]propanoate} (PCT-L) thiophene-based chiral polymer. The effective formation of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…41,42 In particular, Ni (for Co the situation is even worse) forms an oxide layer which can deteriorate the coherence of spin in the current flowing through it. Thus, we developed a method to reduce the oxide film on Ni in situ with the assembly of a monolayer of chiral polymer.…”
Section: Spin Filtering Through Chiral Conductive Polymermentioning
confidence: 99%
“…41,42 In particular, Ni (for Co the situation is even worse) forms an oxide layer which can deteriorate the coherence of spin in the current flowing through it. Thus, we developed a method to reduce the oxide film on Ni in situ with the assembly of a monolayer of chiral polymer.…”
Section: Spin Filtering Through Chiral Conductive Polymermentioning
confidence: 99%
“…Fabrication methods based on highly controlled ultra-high vacuum (UHV) environments or in situ electrochemical control are available. 4,5,[33][34][35][36] Most electrochemical techniques are based on a two-step procedure involving removal of the native oxide by electrochemical reduction, followed by immediate substrate immersion in alkanethiol containing ethanolic solutions. During transfer of the oxide free Ni surface, metal-oxides can form as the substrates are exposed to air.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bengió et al 34 reported the fabrication of n-alkanethiolate SAMs on Ni(111) and polycrystalline Ni surfaces by the electrochemical reduction method in which the electrochemical reduction was performed under either acidic or basic aqueous conditions, while the SAM formation was carried out either in situ or by pulling the substrate through a top layer of neat thiol. Instead of using two separate steps and acidic or basic aqueous electrolyte, Fontanesi et al 35 performed electrochemical removal of the oxide layer with the thiol precursor present in the electrolyte (1 : 0.8, ethanol : water) and reported good quality SAMs. Hoertz et al 14 used three different methods for SAM formation on Ni, Co and Fe substrates, (i) glovebox techniques (freshly evaporated metal transfer to a solution of the SAM precursor without exposure to air), (ii) electrochemical reduction inside a glovebox (oxide removal by electrochemical reduction and SAM formation carried out inside the glovebox), and (iii) deposition of metal via direct metal evaporation followed by a brief exposure in air before immersion into a solution with the SAM precursor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the pulsed mode of the potentiostat and galvanostat techniques gives an interesting chiral system with uniform surface morphology. A prepared Ni surface can be further functionalized for spin dependent electrochemistry [18].…”
Section: Discussionmentioning
confidence: 99%